Formation of Caste System in Coastal Zone: An Ethnographical study - Srikanthan, S. (University of Jaffna, 2015)
This study analyzes formation of caste system in coastal zones as the consequences of ecological and cultural adaptations. Anthropologists use the term ‘cultural adaptation’ to explain that eco- system attributed to determine not only means of subsistence of human but also their entire life. Indeed, adaptation is the way of living population related to the environment so that, they can survive and reproduce. In South Asian context, the different adaptative systems gradually evolved various castes and subcastes. Caste is a unique phenomenon as well as it is a local manifestation of a historical stage in social evolution. In this regard, this exploratory study attempts to discuss the cultural adaptation of caste in coastal areas with special reference to two fishing communities namely karaiyar and Pattinavar inhabited in Jaffna and Coromandel costal zones respectively through ethnographical perspective. The data used in this study were collected from primary and secondary sources. The primary data were recoded through intensive fieldwork undertaken two different fishing villages, one is from Jaffna coast, Sri Lanka in 2012 and another is from Coromandel Coast, Tamil Nadu in 2013. Key informant’s interviews and discussion with both village dwellers are domain tools for primary data collection of this study. However, significant previous studies and authentic documents were used as secondary sources for this study. This study emphasizes that the life and philosophy of fisherfolks are intertwined with land and ecology that shape their lifestyle. The ecological adaption and cultural system of above said fisherfolks contributed to the formation of various sub castes of these fisherfolks at different regions. Further as fishing was considered as an impure occupation, caste status of fishing communities occupied lower hierarchy than castes involved in cultivation, but, they maintained their upper status above other service castes and within them through their origin myth, ethno history and other distinct cultural features.
Keywords: adaptation; subcaste; ethnography